In vivo evaluation of cellular activity in αCaMKII heterozygous knockout mice using manganese-enhanced magnetic resonance imaging (MEMRI) - Hattori, Satoko; Hagihara, Hideo; Ohira, Koji; Aoki, Ichio; Saga, Tsuneo; Suhara, Tetsuya; Higuchi, Makoto; Miyakawa, Tsuyoshi (Frontiers in Integrative Neuroscience, 2013)
The alpha-calcium/calmodulin-dependent protein kinase II (αCaMKII) is a serine/threonine protein kinase predominantly expressed in the forebrain, especially in the postsynaptic density, and plays a key role in synaptic plasticity, learning and memory. αCaMKII heterozygous knockout (HKO) mice exhibit abnormal emotional and aggressive behaviors and cognitive impairments and have been proposed as an animal model of psychiatric illness. Our previous studies have shown that the expression of immediate early genes (IEGs) after exposure to electric foot shock or after performing a working memory task is decreased in the hippocampus, central amygdala, and medial prefrontal cortex of mutant mice. These changes could be caused by disturbances in neuronal signal transduction; however, it is still unclear whether neuronal activity is reduced in these regions. In this study, we performed in vivo manganese-enhanced magnetic resonance imaging (MEMRI) to assess the regional cellular activity in the brains of αCaMKII HKO mice. The signal intensity of MEMRI 24 h after systemic MnCl2 administration reflects functional increases of Mn2+ influx into neurons and glia via transport mechanisms, such as voltage-gated and/or ligand-gated Ca2+ channels. αCaMKII HKO mice demonstrated a low signal intensity of MEMRI in the dentate gyrus (DG), in which almost all neurons were at immature status at the molecular, morphological, and electrophysiological levels. In contrast, analysis of the signal intensity in these mutant mice revealed increased activity in the CA1 area of the hippocampus, a region crucial for cognitive function. The signal intensity was also increased in the bed nucleus of the stria terminalis (BNST), which is involved in anxiety. These changes in the mutant mice may be responsible for the observed dysregulated behaviors, such as cognitive deficit and abnormal anxiety-like behavior, which are similar to symptoms seen in human psychiatric disorders.